Strategy Marketing Mix Born Neo Café at South Pontianak - Cicilia Angelisca; Juliana Juliana; Arifin Djakasaputra (CV. Ulil Albab Corp, 2023)
Along with the development of the times, businesses or businesses engaged in the F&B industry, especially cafes, are growing rapidly. Café is no longer a place to buy food and drinks but also to fulfill one's social needs, namely to increase prestige and recognition. In Indonesia, the current Cafe business, especially in big cities, is growing rapidly, B-Neo Café is one of the cafes built in Pontianak City with a 5 star concept, the business feasibility study at Born-Neo Café aims to analyze whether Born-Neo Café Neo Café is worthy as a business or not based on strategy marketing mix. Based on all analysis and business aspects, including market and marketing aspects in implementing the marketing mix strategy, it can be concluded that Born-Neo Café is a viable and profitable business to run. Suggestions for further research can carry out a marketing strategy using business canvas model analysis, using porter's five forces analysis and strategies for determining segmenting, targeting, positioning.